Longitudinal Assessment of Reading Proficiency Through CRLA: A Three-Year Analysis of Grade 1-3 Learners In SDO- Makati (2022-2025) - P. Casingal, Cyrus; V. Laud, Gizelle; Fe C. Balaba, Maria (International Journal of Educational Review, 2025)
This three-year longitudinal Study addresses a critical gap in understanding reading proficiency development in multilingual educational settings, particularly in post-pandemic recovery in Philippine basic education. The research aimed to analyze the effectiveness of the Comprehensive Rapid Literacy Assessment (CRLA) implementation in tracking and improving reading proficiency among Grades 1-3 learners in SDO Makati from 2022 to 2025, specifically focusing on mother tongue-based instruction and dual-language development. Using a longitudinal research design, the Study examined 18,159 students across 15 elementary schools, implementing pre-test (BOSY) and post-test (EOSY) assessments through CRLA, which evaluated reading proficiency across four levels: Grade Ready, Light Refresher, Moderate Refresher, and Full Refresher. The findings revealed significant improvements across all grade levels, with Grade 1 showing a dramatic reduction in students requiring full refresher intervention from 55.17% to 1.64%, Grade 2 from 32.17% to 0.80%, and Grade 3 demonstrating successful bilingual development with Filipino full refresher needs decreasing from 19.88% to 0.71% and English from 12.43% to 1.16%. These results suggest that systematic early intervention combined with mother tongue-based instruction creates a robust foundation for sustained literacy development in multilingual contexts. The dramatic reductions in students requiring full refresher intervention were statistically significant across all grade levels (p<0.001), with large effect sizes (Cohen's d ranging from 1.45 to 2.13), indicating not only substantial but reliable improvements. The 95% confidence intervals for these improvements (Grade 1: 52.3%-55.7%; Grade 2: 30.2%-32.5%; Grade 3 Filipino: 18.4%-19.9%; Grade 3 English: 10.5%-12.0%) further demonstrate the consistency of these positive outcomes across the student population.